Pembelajaran Direct Instruction Melalui Media Video Terhadap Keterampilan Praktik Shalat Berjamaah - Maslani Maslani (Jurnal Perspektif, 2018)
The purpose of this study was to determine the effect of Direct Instruction learning model through video media on prayer practice skills in congregations in the treated class and those who were not treated. This study used the quasi-experimental method and nonequivalent control group design using two existing classes as samples, Experiments and Control Classes. The technique used to collect quantitative data is in the form of a test. The test is given twice, namely Pretest and Posttest. While for analyzing and processing data is done by statistical techniques. The results of this study were obtained from the use of Direct Instruction models through video media in the class that received treatment obtained by increasing student learning outcomes by 20.99% while those in classes that did not get treatment with conventional models obtaining 19.98% of this data was tested by analyzing data in the form of two average differences obtained by Zhitung 4.31> Ztable 1,645 so that it counts> Ztable. This data shows there are differences in influence between classes received treatment and classes that were not treated. Thus, it can be concluded that there is a significant influence on prayer practice skills in congregation by using the Direct Instruction model through video media for class VII students of SMP Negeri 2 Ciparay.